Development of Augmented Reality-Based History Card Media to Strengthen Chronological Thinking Skills - Brilliantoro Yusuf Ervanda; Rhoma Dwi Aria Yuliantri; Awanis Akalili (Universitas Hamzanwadi, 2026)
Chronological thinking skills are an important foundation in historical thinking skills because they help students understand the relationships between historical events in a coherent, logical, and meaningful manner. However, the results of a needs analysis at SMAN 2 Klaten indicate that students still experience difficulties understanding the sequence of events in the material